Estrutura e ecologia trófica da Ictiofauna da microbacia do Córrego Beija-flor, Estação Ecológica de Jataí, Luiz Antônio, SP - Luiz, Tatiane Ferraz (Universidade Federal de São Carlos, 2014)
The objective of this study was to analyze the structure, composition, trophic ecology and food items shared by the fish fauna in the stream Beija -Flor, located in Jataí Ecological Station ( 21 ⁰ 36'32 .8 " S 47 ⁰ 48'0 .54 " W ), besides characterizing the trophic ecology of the species Hemigrammus marginatus, one of the most abundant in the Beija-Flor stream. The samples of fish were collected monthly from August 2011 to July 2012, using gill nets, trawl nets and baited traps in five sampling stations distributed along the Beija-Flor stream. The fish were fixed in 10% formalin in the field and in the laboratory were identified and subjected to biometric measurements. The stomachs were weighed and transferred to 70% alcohol and stomach contents were examined under a stereomicroscope to the lowest possible taxonomic level. Forty four fish species belonging to 33 genera, 16 families and 5 orders were collected. Most species were accidental ( 43.18 % ), followed by constant species ( 38.64 % ) and accessory (18.18 % ). The diet of 30 species was analyzed. The main dietary habit was insectivorous, followed by omnivorous habits, herbivorous, piscivorous and detritivore. The dietary overlap was high in several species during periods of dry and flood. Hemigrammus marginatus was classified as an insectivore. Food items of autochthonous origin of the orders Ephemeroptera and Trichoptera were more important during the dry season, while the items of allochthonous origin of the order Hymenoptera, were more important in the rainy season. The increase in the quantity and variety of food items during the flooding causes some species of fish to become more generalist and share food resources. Hemigrammus marginatus, Astyanax altiparanae, Metynnis maculatus, Serrapinnus notomelas and Oligosarcus pintoi, have complex of interactions with the food items and can be considered key species for stream Beija- Flor. The results showed that the stream Beija-Flor is a preserved, with high species diversity by being located within the Jataí Ecological Station, but is highly threatened by being surrounded by sugar cane plantations.
Keywords: Peixes de riachos; Bacia do alto Paraná; Sobreposição alimentar; Teia trófica; Rede bipartida; Stream fishes; The upper Paraná basin; Diet; Dietary overlap; Trophic web; Bipartite basal web; CIENCIAS BIOLOGICAS::ECOLOGIA::ECOLOGIA DE ECOSSISTEMAS